Hypoxia-mediated upregulation of MCT1 expression supports the glycolytic phenotype of glioblastomas - Miranda-Gonçalves, V. (2017)
Submitted by José Pereira (jro.pereira@gmail.com) on 2017-07-10T15:20:45Z No. of bitstreams: 1 Hypoxia-mediated upregulation of MCT1 expression.pdf: 6331935 bytes, checksum: 933cae6912c6946cfa38c5eb9ba76332 (MD5)